INFLUENCE OF INSTITUTIONALIZED CARE ON PSYCHOSOCIAL WELL-BEING OF THE ELDERLY IN KENYA: A CASE OF NYUMBA YA WAZEE NAIROBI COUNTY, KENYA - Kago, Moses Kamau; Kavulya, Prof. Joseph; Mutua, Daniel M. (International Journal of Psychology, 2017)
Purpose: The purpose of this study was to determine the influence of institutionalized care on psychosocial well- being of the elderly in Kenya. Methodology: The study adopted a case study research design. The study population comprised of 118 persons who included the institutions managers, staffs and the elderly persons in Nyumba ya Wazee. A census methodology was used for the managers and staffs (50) whereas purposive sampling was used to sample the elderly persons (20) within the institution. The data was collected using structured questionnaires while interview schedules was administered to the aged people within the Home. The collected data was entered and coded into Statistical Package for Social Sciences (SPSS) for analysis. Frequencies, percentages and means was presented. Results: The study found out that institutionalized care for the old was found to influence psychosocial well-being of elderly. The care given to the elderly was found to be very important because it influences their psychosocial well-being and hence improves the lives of the elderly at large. Institution policy framework was found to influence the psychosocial well-being of elderly. Old person placed in the institution for the aged do have relative caregivers though they are also assigned non-relative caregivers. Further it was clear from this study that old people are comfortable with the policy frame work for the institution and they have good attitude towards their caregivers which influences positively towards their psychosocial well-being. Unique Contribution to Theory, Practice and Policy: The study recommended that care institutions should ensure that the elderly have a life satisfaction in terms of the ability to transform negative to positive outcome. The care institution should ensure that the elderly never lack basic needs and their health is good. Institutions should ensure caregivers within the institution are well trained and receive on-the-job training to effectively look after the elderly. The community at large should support the management towards ensuring that the institution provides the care to the elderly.